Malaysia-GCC bilateral trade, macroeconomic indicators and Islamic finance linkages: a gravity model approach - Zainal Abidin, Irwan Shah; Haseeb, Muhammad (2018)
The essential standards of Islam lay extraordinary attention on social equity, consideration and allocation of assets among the have and have not. The main aim of this study was to investigate the effect of macroeconomic indicators such as per capital GDP, inflation, real exchange rate, Islamic financial indicators like No. of Islamic banks and Zakah collection (% of GDP) and distance between capital of Malaysia to GCC countries on bilateral trade between Malaysia and GCC countries. The panel time series date from 1990-2017 was applied. The gravity model approach has been used as a theoretical support. The results of fixed effect and random effect show that the entire variables are statistically significant. However, variable like real exchange rate, inflation and distance found negatively significant, which means that with the increase of these variables the overall bilateral trade among Malaysia and GCC counties will be decrease. On the other side, variables such as per capital GDP, No. of Islamic banks and Zakah collection are found positively related with bilateral trade among Malaysia and GCC countries during the period of study.